Cost-effectiveness of introducing an MF59-adjuvanted trivalent influenza vaccine for older adults in Argentina. Issue 20 (29th April 2020) - Nguyen, Van Hung; Vizzotti, Carla; Uruena, Analia; Giglio, Norberto; Magneres, Cecilia; Richmond, Heather
Abstract: Introduction: Influenza surveillance in Argentina reported influenza-like illness at a rate of 3500/100, 000, a hospitalization rate of 15.5/100, 000, and a death rate of 0.32/100, 000 annually in adults aged over 65 years. The high burden of disease may be due to a combination of immunosenescence and the suboptimal clinical effectiveness of conventional, non-adjuvanted influenza vaccines in this age group. There is a clinical need for more effective influenza vaccines in this population. This study evaluated the cost-effectiveness of an MF59®-adjuvanted trivalent influenza vaccine (aTIV) in adults aged over 65 years in Argentina compared with the non-adjuvanted trivalent influenza vaccine (TIV) used under the current national vaccination policy. Methods: A decision tree cost-effectiveness model was developed to estimate the cost-effectiveness of switching from TIV to aTIV in Argentinian older adults. The model compared cost and health benefits of vaccination in one influenza season from the payer perspective. The main predictions included survival, quality-adjusted survival, and costs. Model inputs were sourced from Argentina or internationally where local data was considered inaccurate. Vaccine efficacy assumptions were extracted from recently published, peer-reviewed scientific literature. Results: Switching from TIV to aTIV would result in 170 deaths averted and 1310 incremental quality-adjusted life years (QALYs) gained. The incremental cost-effectiveness ratio per QALY was US 2660.59 from the payer perspective. In all sensitivity analyses, aTIV remained highly cost-effective. The probabilistic sensitivity analyses showed a 95% CI per QALY of US 113.74–7721.67. Conclusion: Introducing an adjuvanted influenza vaccine in Argentina is potentially beneficial and cost-effective relative to the currently-used TIV through the reduction of disease burden and utilization of healthcare resources.